THE USE OF SCIENTIFIC APPROACH USING GUIDED INQUIRY MODEL IN IMPROVING THE LEARNING OF SCIENCE ABOUT THE CHARACTERISTICS OF LIGHT FOR THE FIFTH GRADE STUDENTS OF SD NEGERI SRUSUH JURUTENGAH IN THE ACADEMIC YEAR OF 2016/2017. - Nurhayati, Siti; Susiani, Tri Saptuti; Salimi, Moh (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use Of Scientific Approach Using Guided Inquiry Model In Improving The Learning Of Science About The Characteristics Of Light For The Fifth Grade Students Of SD Negeri Srusuh Jurutengah In The Academic Year Of 2016/2017. The objective of this research is to improve the learning of IPA about the characteristics of light for the fifth grade students of SD Negeri Srusuh Jurutengah in the academic year of 2016/2017. This research is a collaborative Classroom Action Research (CAR). Subjects of the research were the teacher and 21 students. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. The results of this research show that the use of scientific approach using guided inquiry model can improve the learning of science.Keywords: Scientific Approach, guided inquiry, Learning of science.